Exploring the relationship between students’ conceptual understanding and model thinking in quantum optics - Ubben, Malte; Bitzenbauer, Philipp (Frontiers in Quantum Science and Technology, 2023)
Learning quantum physics is essential for understanding the physical world. However, learning about quantum phenomena and principles poses a challenge as many of the phenomena that are observed at the quantum level cannot be directly observed or intuitively understood in terms of classical physics or thinking. Models play an important role in learning quantum physics by providing conceptual frameworks and visual representations that allow reasoning about and predicting the behavior of quantum systems. Therefore, understanding models is an essential part of learning quantum physics. In this article, we report the results of an exploratory survey study (N = 116) investigating the relationship between secondary school students’ conceptual understanding and model thinking in quantum optics with a particular focus on photons. The findings suggest a strong positive correlation between students' functional understanding of the photon model and their conceptual understanding of quantum optics. This study contributes to our understanding of how students learn and make sense of quantum concepts through the use of models and may inform the development of instructional strategies for quantum physics education and outreach.